2013
DOI: 10.1002/ana.23897
|View full text |Cite|
|
Sign up to set email alerts
|

Dravet syndrome patient‐derived neurons suggest a novel epilepsy mechanism

Abstract: OBJECTIVE Neuronal channelopathies cause brain disorders including epilepsy, migraine and ataxia. Despite the development of mouse models, pathophysiological mechanisms for these disorders remain uncertain. One particularly devastating channelopathy is Dravet Syndrome (DS), a severe childhood epilepsy typically caused by de novo dominant mutations in the SCN1A gene encoding the voltage-gated sodium channel Nav1.1. Heterologous expression of mutant channels suggests loss-of-function, raising the quandary of how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
179
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(201 citation statements)
references
References 38 publications
12
179
1
Order By: Relevance
“…In contrast, two other studies reported increased excitability in iPSC-derived neurons carrying SCN1A mutations. Liu et al (2013b) found that a deletion of exon 14, which affects transmembrane segments 2-4 in domain II, and a truncation mutation (Y325X) within the pore loop of domain I confer increased sodium currents and hyperexcitability in both bipolar and pyramidal iPSC-derived neurons. Similarly, a missense DS-causing mutation (F1415I) resulted in increased excitability in glutamatergic neurons (Jiao et al 2013).…”
Section: Patient-specific Ipsc-derived Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, two other studies reported increased excitability in iPSC-derived neurons carrying SCN1A mutations. Liu et al (2013b) found that a deletion of exon 14, which affects transmembrane segments 2-4 in domain II, and a truncation mutation (Y325X) within the pore loop of domain I confer increased sodium currents and hyperexcitability in both bipolar and pyramidal iPSC-derived neurons. Similarly, a missense DS-causing mutation (F1415I) resulted in increased excitability in glutamatergic neurons (Jiao et al 2013).…”
Section: Patient-specific Ipsc-derived Neuronsmentioning
confidence: 99%
“…Similarly, a missense DS-causing mutation (F1415I) resulted in increased excitability in glutamatergic neurons (Jiao et al 2013). It was proposed that compensatory overexpression of other ␣-subunits in response to loss of Na V 1.1 may underlie the increased sodium currents in neurons derived from DS patient-specific iPSCs (Liu et al 2013b).…”
Section: Patient-specific Ipsc-derived Neuronsmentioning
confidence: 99%
“…29,30 In contrast, a study using induced pluripotent stem cells from 2 patients with Dravet syndrome suggested that the SCN1A mutations led to increased excitability of both pyramidal neurons and interneurons, independent of inhibitory inputs. 31 A recent review that compiled all 1257 known pathogenic SCN1A mutations found that 82% of known mutations have been reported in only 1 family. 20 Thus, the majority of identified SCN1A mutations are newly described, as was the case in all of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…iPSCs provide a particularly attractive model for neurologic disease, where access to live human tissue suitable for culture is extremely limited. Some recent studies have used iPSCs to model epilepsy mechanisms in Dravet syndrome [136]. These data suggest that epilepsy syndromespecific iPSC-derived neurons are useful for modeling epileptic-like hyperactivity, which offers a platform for screening new antiepileptic therapies.…”
Section: Future Directionsmentioning
confidence: 97%